Dr. Rolston, Sir John Templeton and Jack Templeton - Lehr, Donald, photographer (Colorado State University. Libraries, 2003)
Photograph featuring Dr. Rolston at New York Press Conference on May 19, 2003.
Keywords: Templeton laureates; Colorado State University; philosophy professor; Templeton Prize; Rolston, Holmes, 1932-2025